Long-term outcome following total knee arthroplasty: a controlled longitudinal study. Issue 5 (29th July 2008) - Cushnaghan, J; Bennett, J; Reading, I; Croft, P; Byng, P; Cox, K; Dieppe, P; Coggon, D; Cooper, C
Abstract : Objectives: To assess long-term outcome and predictors of prognosis following total knee arthroplasty (TKA) for osteoarthritis. Methods: We followed-up 325 patients from 3 English health districts approximately 6 years after TKA, along with 363 controls selected from the general population. Baseline data, collected by interview and examination, included age, sex, comorbidity, body mass index (BMI), functional status and preoperative radiographic severity of osteoarthritis. Functional status at follow-up was assessed by postal questionnaire. Predictors of change in physical function were analysed by linear regression. Results: Between baseline and follow-up, patients reported an improvement of 6 points in median Short Form 36 Health Survey (SF-36) physical function score, whereas in controls there was a deterioration of 14 points (p<0.001). Median SF-36 vitality score declined by 10 points in patients and 5 points in controls (p = 0.005), while their median SF-36 mental health scores improved by 12 and 13 points, respectively (p = 0.2). The improvement in physical function was smaller in patients who were obese than in patients who were non-obese, but compared favourably with a substantial decline in the physical function of obese controls. Better baseline physical function and older age predicted worse changes in physical function in patients and controls. Improvement in physical function tended to be greater in patients with more severe radiological disease of the knee, and was less in those who reported pain at other joint sites at baseline. Conclusions: Improvements in physical function following TKA for osteoarthritis are sustained beyond 5 years. The benefits are apparent in patients who are obese as well as non-obese, and there seems no justification for withholding TKA from obese patients solely on the grounds of their body mass index.